The influence of sodium salt of 3-(2-oxo-3-phenyl-2H-[1,2,4]triazyno[2,3-c]quinazolin-6-yl) propane acid on the morphological picture of rat’s heart in the background of hypokinesia. - Saenko, A. V.; Stratiychuk, A. S.; Stepaniuk, G. I.; Kovalenko, S. I. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Long hypokinesia causes significant impairment in humans: a decrease in muscle mass redistribution of blood and fluid in general, decrease of energy, reducing load on the heart and endocrine glands, oppression of mitochondria and aerobic metabolism, development of respiratory distress syndrome. Objective. The aim of the study was to characterize the impact of the connection MT-279 compared to bemityl on the morphological picture rat heart in the background of hypokinesia. Methods. Hypokinesia was modeled by rats within 15 days (16 hours/day) in individual wooden casks. The rats were divided into 4 groups of 7 species each: I - intact animals; II - rats with HC without correction (control group, which have introduced equivalent amount of 0.9% NaCl); III - the animals with the HC, which once daily (from 1 to 15 days of research) were introduced inside with connection MT-279 in the dose of 2.5 mg/kg, which was equal to the for swimming test; IV - rat with the HC, which similarly, in/in, was introduced Bemityl dose 33.0 mg/kg, which makes it for swimming testometric the control group received a dose of 0.9% NaCl solution. Results and Conclusion. The 15-day hypokinesia leads unstable hemodynamics, atrophic and destructive changes in skeletal muscle fibers and myocardium of rats. Exchange rate of 15-day rat on the background of hypokinesia connection MT-279 (2.5 mg/kg, in/on), as bemityl (33.0 mg/kg), in/on), accompanied by expressive adaptive changes in the myocardium of animals: the normalization of hemodynamics and preservation of the structure of cardiomyocytes. Connection MT-279, like bemityl, promotes reduction of destructive changes in the muscle fibres and endoteliya walls of microcirculatory vessels of the heart muscle of rats in conditions of the 15-day hypokinesia.